Conceptual grounds for administering education process in modern world - Azhazha, Maryna; Zhukova, Oksana; Peliova, Jana; Shkrabiuk, Veronika (Scientific notes of the pedagogical department, 2021)
The article based on the analysis of the literature, identifies the general patterns of development of lifelong learning. The need for lifelong learning is considered; basic competencies that help in this, as well as the relevance of the choice and use of these competencies in modern society. It is investigated that in the conditions of European integration of Ukraine and innovative management under the influence of social and economic transformations requirements to the quality of professional training of future experts grow. Balanced management of the modernization of higher education and the market of educational services it provides will provide a strong, high level of personal and professional competence with strong, innovative knowledge, personal and professional competence, strong human potential. The key problems of post-industrial production, the technologies of which are constantly updated, have been identified, and many specialists are forced to retrain, change qualifications or the profession in general. Therefore, lifelong learning becomes relevant, which is the basis for the self-realization of each individual, a factor in the formation of powerful human capital, a determinant of the economic prosperity of Ukraine. The fundamental principles of lifelong learning are studied. The study analyses the methodological aspects of lifelong learning, which reveal the spatial approach (which allows you to analyse the interdependent continuous, subordinate socio-political and cultural processes); multilevel approach (which analyses the relationships and interactions of the reproduction of human capital at the micro-, meso, and macro levels, taking into account global, global, regional and local factors influencing the political, economic, socio-cultural trends of intellectual society). The expediency of applying the experience of the European Union countries and, in particular, Slovakia in Ukraine to increase the efficiency of lifelong education administration is substantiated.